Organization Sustainability and Employee Performance in a Literature Review - Agustian Zen (Formosa Journal of Multidisciplinary Research, 2023)
The purpose of the study is to see and describe from the review literature related to the variables present in this study. The existing problems are the elaboration of the review literature obtained by the researcher. The method used is qualitative with literature review, where the literature review of researchers and the findings of  review articles are related to the  results of each variable, employee trust is significant with employee trust, furthermore work life balance is also significant with employee performance, transactional leadership is significant with large presentations and there is also insignificant with minimal results, then  Employee Performance with Organization Sustainability did not find direct results that stated significant or insignificant.